Rhabdomyolysis and acute kidney injury following multiple bee stings in a child: A case report - Abdul Rauf; Ajay Vijayan; V M Hashitha; Shaji Thomas John; Jayameena Peringat (Wolters Kluwer Medknow Publications, 2021)
Multiple bee stings commonly cause allergic and anaphylactic reactions, but it can also cause serious complications such as intravascular hemolysis, rhabdomyolysis, acute kidney injury (AKI), and even death. Mortality related to AKI following multiple bee stings can be as high as 25%. Hence, patients should be monitored for rhabdomyolysis and AKI during the first few days following the stings. We report the case of a 3-year-old boy who developed AKI due to rhabdomyolysis following multiple bee stings. He required pediatric intensive care support including mechanical ventilation and renal replacement therapy in the form of multiple sessions of hemodialysis. His renal function improved gradually. He was discharged after 3 weeks with normal renal function and he remained well on 6 months follow up. The treatment of multiple bee stings should be considered as a medical emergency, and these cases should be admitted in a pediatric intensive care unit and monitored for at least 48 h for the occurrence of rhabdomyolysis, myoglobinuria, and AKI.